Liquidation with nonlinear float‐dependent price impact. Issue 2 (7th February 2019) - Guasoni, Paolo; Sanjari, Ali
Abstract: This paper solves the infinite‐horizon optimal liquidation problem in a market with float‐dependent, nonlinear temporary price impact. The investor's value function and optimal strategy are identified as the unique classical solutions of nonlinear parabolic partial differential equations. Depending on the price impact parameters, liquidation may require finite or infinite time.